Perkembangan Konsep Perjanjian Production Sharing Contract Dalam Mekanisme Pengolahan Minyak dan Gas di Indonesia - Mohammad Choirul Anam; Retno Catur Kusuma Dewi; Angga Pramodya Pradhana (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
This research aims to determine the development of the concept of agreements in production sharing contracts in the oil and gas processing sector based on legal principles in Indonesia. This research uses normative juridical research which uses statutory regulations as a secondary data source. Apart from that, journals, articles, news portals (websites) were also used as supporting sources in this research. Based on the research results, it was found that the development of the concept of production sharing contracts in the oil and gas processing sector in Indonesia was initially introduced by Ibnu Sutowo. Then as time went by it developed up to 4 (four) changes. Even though in its development there have been changes, the concept used in the agreement remains the same, the only difference is in the type of agreement. The concept of a production sharing agreement can be applied in Indonesia because it is simpler, easier to understand by the public, more cost effective; compared to the “Profit Sharing” mechanism. The amount of "Production Sharing" should be close to the gross figure of the amount of "Production Sharing", so that oil and gas investors are not surprised by the new formulation. Because they are used to these numbers, what they live with now is still mutually beneficial. The possibility of applying taxes in the "Production Sharing" mechanism, can be applied at the beginning of activities (subject to Cost Recovery), or imposed on gross production results that come out of oil and gas wells. The formulation of the amount and type of tax needs to be studied jointly between the Director General of Taxes, SKKMigas, and oil and gas investor representative bodies. This is to continue to attract oil and gas investors to carry out oil and gas exploration and production in Indonesia